An Analysis of PT Bank CDE's Capacity to Implement the Climate Risk and Management Scenario (CRMS) - Inggar Rayi Agatha; Aria Farah Mita (Greenation International Journal of Economics and Accounting, 2025)
Climate change has become a global issue that significantly impacts the banking sector, particularly in the management of credit portfolios that are vulnerable to both physical and transition risks. These risks may affect asset quality and the overall financial stability of banks. Therefore, it is essential for banking institutions to demonstrate the capacity in managing such risks through scenario based approaches, such as the Climate Risk Management Scenario (CRMS). This study aims to analyze the capacity of PT Bank CDE in implementing CRMS as part of its climate risk management strategy for its credit portfolio. A qualitative approach with a case study strategy was employed. Data collection was conducted through semi structured interviews as the primary data source and document analysis of regulatory guidelines and the company’s sustainability reports as secondary data. The findings indicate that PT Bank CDE is at a fundamental stage in implementing CRMS. This organizational capacity is reflected in the establishment of an Environmental, Social, and Governance (ESG) Management unit, cross functional collaboration (involving ESG Management, IT, Business, and the ESG Subcommittee), and the adoption of the Three Lines Model principle, although it has not yet been formally institutionalized. These findings suggest an initial commitment to integrating climate risk into the company’s risk governance system.